Challenges in estimating the encapsulation efficiency of proteins in polymersomes - Which is the best method? - Jorge Javier Muso-Cachumba; Grace Ruiz-Lara; Gisele Monteiro; Carlota de Oliveira Rangel-Yagui (Universidade de São Paulo, 2023)
Abstract Polymersomes are nanometric vesicles that can encapsulate large and hydrophilic biomolecules, such as proteins, in the aqueous core. Data in literature show large variation in encapsulation efficiency (%EE) values depending on the method used for calculation. We investigated different approaches (direct and indirect) to quantify the %EE of different proteins (catalase, bovine serum albumin-BSA, L-asparaginase and lysozyme) in Pluronic L-121 polymersomes. Direct methods allow quantification of the actual payload of the polymersomes and indirect methods are based on the quantification of the remaining non-encapsulated protein. The protein-loaded polymersomes produced presented approximately 152 nm of diameter (PDI ~ 0.4). Higher %EE values were obtained with the indirect method (up to 25%), attributed to partial entanglement of free protein in the polymersomes poly(Ethylene Glycol) corona. For the direct methods, vesicles were disrupted with chloroform or proteins precipitated with solvents. Reasonable agreement was found between the two protocols, with values up to 8%, 6%, 17.6% and 0.9% for catalase, BSA, L-asparaginase and lysozyme, respectively. We believe direct determination is the best alternative to quantify the %EE and the combination of both protocols would make results more reliable. Finally, no clear correlation was observed between protein size and encapsulation efficiency.